Determinan harga saham sektor properti dan real estat di bursa efek indonesia - Nuryasman, Nuryasman; Yessica, Yessica (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This study aims to examine the effect of exchange rate (USD/IDR), inflation and BI Rate to real estate and property stock that listed in BEI from January 2010 ? December 2015 with 34 samples. Statistical analysis tool used was Eviews6 with the panel regression analysis and purposive sampling method. This study shows that together the USD / IDR exchange rate, inflation rate and SBI interest rate significantly influence the stock price. While partially only exchange rate USD / IDR and SBI interest rate which have significant effect to stock price.